Enhancing Learning Motivation through Interactive Video Technology in Islamic Religious Education - Zahwatus Syahidah; Ngatmin Abbas; Arif Effendi (Ashlach : Journal of Islamic Education, 2026)
This study is motivated by the limited empirical research on the use of interactive video-based learning technology in Islamic Religious Education (IRE), despite its potential contribution to enhancing students’ learning motivation in the digital era. The study aims to analyze the effect of interactive video-based learning technology on students’ learning motivation in Islamic Religious Education. The research adopts a quantitative correlational design, involving 30 eleventh-grade students of SMA Al Islam 1 Surakarta selected through a total sampling technique. Data were collected using structured questionnaires measuring the utilization of interactive video-based learning technology and students’ learning motivation. Prior to data collection, the instruments were tested for validity and reliability. The data were analyzed using descriptive statistics and simple linear regression with the assistance of IBM SPSS Statistics version 31. The findings reveal that both the utilization of interactive video-based learning technology and students’ learning motivation were categorized at a moderate level. Furthermore, the regression analysis indicates that interactive video-based learning technology has a positive and statistically significant effect on students’ learning motivation (p = 0.012 < 0.05), with a coefficient of determination (R²) of 0.206, indicating that interactive video technology contributes 20.6% to the variance in learning motivation. These findings support the Cognitive Theory of Multimedia Learning, which emphasizes the effectiveness of multimedia-based instruction in facilitating meaningful learning experiences. The study concludes that interactive video-based learning technology plays an important role in enhancing students’ learning motivation in Islamic Religious Education. The implications of this study include theoretical contributions to the literature on educational technology and Islamic education, as well as practical recommendations for teachers and schools to integrate interactive video learning into instructional practices. Additionally, future research is encouraged to investigate other factors influencing learning motivation and to involve larger and more diverse samples across educational settings